Caries Risk Assessment and Prevention: - Michael J. Kanellis, DDS, MS (Blackwell Synergy, 2000)
Tfris review updates the evidence regarding caries risk assessment for infants, toddlers, and preschool children and formulates recommendations for preventive strategies for WlC, Head Start, and Early Head Start.